Analyzing the procedure of general banking activities of Standard Bank Ltd. - Rahman, Mustafizur; BRAC Business School, BRAC University (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Master of Business Administration,2014.